Electron Microscopical Investigation of Interdiffusion and Phase Formation at Gd2O3/CeO2- and Sm2O3/CeO2-Interfaces - Rockenhäuser, Christian (Springer, 2015)
Christian Rockenhäuser adresses phase formation and cation interdiffusion of the GdxCe1-xO2-x/2-and SmxCe1-xO2-x/2-material systems at temperatures ranging from 970 to 1270°C. Diffusion couples with CeO2/Sm2O3 and CeO2/Gd2O3 interfaces were fabricated for the investigations. The resulting reaction phases were investigated utilizing transmission electron microscopy (TEM) and allow conclusions regarding the phase diagrams in the examined temperature range. A miscibility gap can be ruled out for GdxCe1-xO2-x/2 across the whole composition range. Cation interdiffusion coefficients were determined for both material systems by measuring and evaluating concentration profiles at the material interfaces. The activation enthalpies for interdiffusion were calculated using the temperature dependence of the interdiffusion coefficients. The study for the first time compiles comprehensively the previous results regarding the phase diagrams of the two material systems since 1923.